THE CHRONIC PSYCHO-EMOTIONAL STRESS IS ACCOMPANIED BY ENDOTHELIAL DYSFUNCTION, PROMOTES VASCULAR REMODELING AND REDUCTION OF CEREBRAL PERFUSION - I. S. Lutskiy (Кубанский научный медицинский вестник, 2015)
The influence of the chronic psycho-emotional stress (CPES) on the formation of the endothelial dysfunction (ED), the processes of vascular remodeling and the indicators of cerebral hemodynamics was explored. As a model of the effect of CPES 160 railroad engineers were examined. As a control, 100 healthy volunteers were examined. It is shown that the effect of CPES accompanies increasing production of the central (adrenocorticotropic) and the peripheral (cortisol, corticotropin) stress hormones. The effect of stress system has the serial reaction: periods of activation, resistance and allostasis. In the early stages of the stress impact the formation of ED take place. It is characterized by decreased secretion of the vasodilator NO and increasing production of the vasoconstrictor endothelin-1. ED stimulates vascular remodeling. In the large vessels of elastic type remodeling leads to thickening of the intima-media complex. In the vessels of muscular type is an increase in vascular tone, increased peripheral resistance, which is accompanied by a decrease in blood flow velocity.